Formation and development of the national parks legal concept - Zhloba, Albert A. (Journal of the Belarusian State University. Law, 2021)
The article is devoted to the formation and development of the international and Belarusian legal concept of national parks. The importance of harmonising approaches to the definition and status of national parks, their role in the system of protected areas is substantiated. The conclusion is drawn on the advisability of clarifying the Belarusian legal concept of the national park on the basis of general and special features of this category. The author formulates definition of the given term taking into account the requirements of the international community for this form of especial environmental protection (IUCN category II).
Keywords: national park; especially protected natural area; natural areas conservation; environmental protection; International Union for Conservation of Nature